Redox mechanisms of cardiomyocyte mitochondrial protection - Bartz, Raquel R.; Suliman, Hagir B.; Piantadosi, Claude A. (Frontiers in Physiology, 2015)
Oxidative and nitrosative stress are primary contributors to the loss of myocardial tissue in insults ranging from ischemia/reperfusion injury from coronary artery disease and heart transplantation to sepsis-induced myocardial dysfunction and drug-induced myocardial damage. This cell damage caused by oxidative and nitrosative stress leads to mitochondrial protein, DNA, and lipid modifications, which inhibits energy production and contractile function, potentially leading to cell necrosis and/or apoptosis. However, cardiomyocytes have evolved an elegant set of redox-sensitive mechanisms that respond to and contain oxidative and nitrosative damage. These responses include the rapid induction of antioxidant enzymes, mitochondrial DNA repair mechanisms, selective mitochondrial autophagy (mitophagy), and mitochondrial biogenesis. Coordinated cytoplasmic to nuclear cell-signaling and mitochondrial transcriptional responses to the presence of elevated cytoplasmic oxidant production, e.g. H2O2, allows nuclear translocation of the Nfe2l2 transcription factor and up-regulation of downstream cytoprotective genes such as heme oxygenase-1 which generates physiologic signals, such as CO that up-regulates Nfe212 gene transcription. Simultaneously, a number of other DNA binding transcription factors are expressed and/or activated under redox control, such as Nuclear Respiratory Factor-1 (NRF-1), and lead to the induction of genes involved in both intracellular and mitochondria-specific repair mechanisms. The same insults, particularly those related to vascular stress and inflammation also produce elevated levels of nitric oxide, which also has mitochondrial protein thiol-protective functions and induces mitochondrial biogenesis through cyclic GMP-dependent and perhaps other pathways. This brief review provides an overview of these pathways and interconnected cardiac repair mechanisms.